A 3-year-old child with multifocal (thoracoabdominal) primary neuroblastoma: A case report and literature review - Ayesha Rahmat; Swaminathan Keerthivasagam; Sajid Qureshi; Puja Bathala; Mukta Ramadwar; Gramani Arumugam Vasugi; Harshavardhan Mahalingam; Vasundhara Patil; Dhaarani Jayaraman; Julius Xavier Scott (Elsevier, 2024)
Introduction: Multifocal primary neuroblastoma in the non-infantile age group is rare, posing challenges in risk stratification and surgery. Case report: A 3-year-old girl presented with an abdominal mass and elevated urinary vanillylmandelic acid (218 mg/l). Positron emission tomography - computed tomography showed fluorodeoxyglucose-avid masses in the left suprarenal and posterior mediastinum with regional paraortic nodes. A biopsy of the suprarenal and thoracic masses was suggestive of ganglioneuroblastoma and ganglioneuroma. She was stratified as an intermediate risk, with the bone marrow being uninvolved and non-amplified MYCN. Gross tumor resection was achieved at all the sites after 2 cycles of neoadjuvant chemotherapy. She received 2 more cycles of adjuvant chemotherapy and has been disease-free for 3 years. Conclusion: Multifocal primaries in the non-infantile age group have favorable biological features and a good outcome.